Penerapan Media Pembelajaran Flash Card dalam Meningkatkan Hafalan Mufrodat Bahasa Arab Siswa Kelas IV Madrasah Ibtidaiyah Swasta Tarbiyah Islamiyah Jelutung Kota Jambi - Putri Nilma Sopha (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This articel discusses improving the ability to memorize the mufrodat of class IV students in the Arabic language subject material My Aspirations by applying flash card learning media in the private Ibtidaiyah Madrasah Tarbiyah Islamiyah Jelutung, Jambi City. This research uses the classroom action method which refers to the Kemmis and MC models. Taggart went through four stages, namely: (1) planning, (2) action, (3) observation and (4) reflection. This research consisted of initial observations and 2 cycles. The data analysis technique used in this research is qualitative and quantitative data analysis. The research sample was class IV students at MIS Tarbiyah Islamiyah Jelutung, Jambi City in 2024/2025, totaling 14 people. The aim of this research is (1) by applying flash card media, it can improve class IV students' memorization of mufrodat in Arabic language subjects about my dreams. (2) the ability to memorize mufrodat in Arabic language lessons regarding ideals can be increased through the application of learning media flash cards. Data collection techniques in this research use observation sheets, tests and documentation. The results of this study stated that there was an increase in the ability to memorize mufrodat, this was proven by the pre-cycle percentage which was 37%, then the percentage of cycle I meeting I showed 43% of students who completed it, then cycle I meeting II was at 50%, cycle I experienced an increase but did not increase rapidly and had not yet reached the percentage of completeness, then cycle II, meeting I was 64%, had not yet reached the percentage of completeness, then continued in cycle II, meeting II showed 78% of students had completed. The findings of this research are that by applying flash card media you can improve your ability to memorize Arabic language subjects with my dream material.